A novel framework for development and optimisation of future electricity scenarios with high penetration of renewables and storage. (15th September 2019) - Gaete-Morales, Carlos; Gallego-Schmid, Alejandro; Stamford, Laurence; Azapagic, Adisa
Highlights: FuturES framework optimises electricity scenarios with high renewables penetration. Reservoir and concentrating solar power modelled based on storage value. Feasible scenarios created with 81–100% renewables by 2050. Long-term energy storage helps to achieve low electricity costs. Abstract: Although electricity supply is still dominated by fossil fuels, it is expected that renewable sources will have a much larger contribution in the future due to the need to mitigate climate change. Therefore, this paper presents a new framework for developing Future Electricity Scenarios (FuturES) with high penetration of renewables. A multi-period linear programming model has been created for power-system expansion planning. This has been coupled with an economic dispatch model, PowerGAMA, to evaluate the technical and economic feasibility of the developed scenarios while matching supply and demand. Application of FuturES is demonstrated through the case of Chile which has ambitious plans to supply electricity using only renewable sources. Four cost-optimal scenarios have been developed for the year 2050 using FuturES: two Business as usual (BAU) and two Renewable electricity (RE) scenarios. The BAU scenarios are unconstrained in terms of the technology type and can include all 11 options considered. The RE scenarios aim to have only renewables in the mix, including storage. The results show that both BAU scenarios have a levelised cost of electricity (LCOE) lower than, or equal to, today's costs (72.7–77.3 vs 77.6/MWh) and include 81–90% of renewables. The RE scenarios are slightly more expensive than today's costs (81–87/MWh). The cumulative investment for the BAU scenarios is 123-145 bn, compared to 147-157 bn for the RE. The annual investment across the scenarios is estimated at 4.0 ± 0.4 bn. Both RE scenarios show sufficient flexibility in matching supply and demand, despite solar photovoltaics and wind power contributing around half of the total supply. Therefore, the FuturES framework is a powerful tool for aiding the design of cost-efficient power systems with high penetration of renewables.